2015
DOI: 10.1016/j.cell.2015.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Is Required for the Neural Representation and Control of Movement Vigor

Abstract: Progressive depletion of midbrain dopamine neurons (PDD) is associated with deficits in the initiation, speed, and fluidity of voluntary movement. Models of basal ganglia function focus on initiation deficits; however, it is unclear how they account for deficits in the speed or amplitude of movement (vigor). Using an effort-based operant conditioning task for head-fixed mice, we discovered distinct functional classes of neurons in the dorsal striatum that represent movement vigor. Mice with PDD exhibited a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
303
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(353 citation statements)
references
References 47 publications
34
303
4
Order By: Relevance
“…For example, rodents may be trained to manipulate a lever by automatically rewarding them for correct movements (Slutzky et al, 2010;Panigrahi et al, 2015). The outcomes of such tasks are not necessarily discrete (as in, for example, a lever press task), as the amplitude and direction of the movement can be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rodents may be trained to manipulate a lever by automatically rewarding them for correct movements (Slutzky et al, 2010;Panigrahi et al, 2015). The outcomes of such tasks are not necessarily discrete (as in, for example, a lever press task), as the amplitude and direction of the movement can be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Modulatory actions of DA mediate longer time-scale control of motivational salience, vigor and social behavior (52 Gunaydin, 2014, 1535–1551, 53). However, DA neurons mediate faster, discrete DA synaptic responses, in addition to volume transmission.…”
Section: Synaptic Dopamine Signaling In the Striatummentioning
confidence: 99%
“…MitoPark mice, which have progressive loss of SN to DA dopamine neurons (Ekstrand et al, 2007), show impairments in this task, and optogenetic inhibition of the nigrostriatal pathway induced similar impairments such that subjects took longer to complete a criterion number of trials. Electrophysiological recording from the neurons in this region showed that DMS neurons appear to be both representing and controlling movement vigor in this task (Panigrahi et al, 2015). This is in line with another recent study which used a self-paced nose poking paradigm to demonstrate that overall reward payoff expectancy as well as response vigor appear to be represented in the DS (A.…”
Section: Activational Components Of Motivationmentioning
confidence: 99%
“…Drui et al, 2014). Specifically, recent experiments which monitor in vivo activity within the dorsal striatum in awake behaving animals performing motivated operant behavioral tasks have demonstrated that this region appears to be important for representing and modulating response vigor (Panigrahi et al, 2015; A. Y. Wang et al, 2013).…”
Section: Activational Components Of Motivationmentioning
confidence: 99%